Cytomorphological Study of Body Effusions - Dr. GEETA PACHORI; Dr. SONIYA SANAADHYA; Dr. MANISHA JAIN; Dr. SAROJ PACHORI; Dr. TUSHAR BAYLA (International Journal of Pharma and Bio Sciences, 2018)
Cytological examination of the fluids along with physical examination helps the pathologist to identify specific etiologic agent, to follow the natural process of disease and to monitor the response to therapy. The present study was carried out in Department of Pathology, J.L.N. Medical College and Associated group of Hospitals, Ajmer (Rajasthan) over a period of 3 years from July 2013 to June 2016. Total of 434 cases of serous effusions were studied comprising, 232(53.22%) cases of pleural fluids, 177 (41.01%) cases of ascetic fluids, 21 (04.83%) cases of pericardial fluids and 4 (00.92%) cases of synovial fluids. There were 263(60.6%) males and 171(39.4%) females. 379(87.32%) cases were non malignant, 47(10.83%) cases were of malignant effusion, 08(01.84%) cases were of atypical and suspicious.The present study gives us an insight in understanding the malignant and non-malignant conditionsand the most useful test in establishing the diagnosis of body effusion is fluid cytology. The correlation between clinical examination and cytological study is considered an essential step in diagnosis of disease and its progression.